Entre o Parlamento e a Corte: resposta legislativa diante da atuação judicial - Tárcia Helena Dias de Oliveira (2023)
The work starts from the readings that question the conception that it is up to the Courts to offer the final solution to the questions that are posed. Undoubtedly, the Judiciary is a relevant player, but not as a holder of the ability to silence the other participants involved in the construction of constitutional meaning. The theory of Constitutional Dialogues is the theoretical contribution that supports, in this work, the analysis of the relationship between the Legislative and Judiciary Powers and how both have been inserted, in the national scenario, in the last 10 years, as actors capable of interpreting and applying the Constitution. The key used to scale the dialogue between Parliament and the Court is the legislative response. Thus, we will evaluate the types of legislative response that the National Congress has offered to the decisions of the STF. For a better understanding of the categorization that is intended to operate, some clippings should be clarified. In this work, we will not address any kind of reaction by Congress to a Judicial position. The focus of the research is the legislative response, that is, the cases in which the Parliament uses the legislative process (or fails to do so), to dialogue with a thesis proposed by the Court. We group Congressional legislative responses into three categories: (1) situations in which the Legislature does not move the legislative process after a judicial position (legislative inertia); (2) situations in which the Parliament positive, circumvents or adapts to the judicial understanding, through law or even a Constitutional Amendment (legislative accommodation) and (3) cases in which the parliamentarians overcome the judicial decision, responding through activism legislation legislative overcoming). At the end of the research, the analysis of the “secret budget” case allows verifying the dynamics of the relationship between Congress and the Supreme Court and confirming the constant interaction between the powers, in addition to reaffirming the inexistence of a definitive final word in the elaboration of the definition of the Constitution.